The design of IPT system for multiple kitchen appliances using class E LCCL circuit - N. X. Yin; Shakir Saat; S. H. Husin; Y. Yusop; M. R. Awal (Institute of Advanced Engineering and Science, 2020)
Since many years ago, kitchen appliances are powered up by cable connected. This create a troublesome case as wire might tangle together and cause kitchen table messy. Due to this, wireless power technology (WPT) is introduced as its ability is to transmit power to load without physical contact. This leads to cordless solution better in safety as the product can be completely seal, highly expandable power range. This work focuses on the design of WPT based on inductive approach to power up multiple kitchen appliances. The selection of inductive approach over its partners capacitive and acoustic is mainly due to high power efficiency. Class E inverter is proposed here to convert the DC to AC current to drive the inductive link. A 1 MHz operating frequency is used. To ensure the circuit is robust with load variations, an LCCL impedance matching is proposed. This solution is table to maintain the output power if there is a slight change in load impedance. Finally, the developed prototype is able to supply 50V utput which can achieve power transmission up to 81.76%.